Do first-time avian migrants know where they are going: the clock-and-compass concept today - Chernetsov, Nikita; Utvenko, Gleb (Frontiers in Physiology, 2025)
What if your life depended on finding a place you’ve never been—without a GPS device, a guide, or any way of knowing where to go? For young songbirds, this is the reality of their first migration. While this once puzzled researchers studying bird migration, advances in the field have since uncovered that many songbirds rely on an inherited genetic program to guide their remarkable solo journeys. Today, the most widely accepted theory explaining how young birds of species that migrate solitary and do not follow experienced conspecifics find their way to wintering grounds is the ‘clock-and-compass’ concept. According to this concept, naïve migrants follow a certain compass direction for a pre-defined period. In the simplest case, when the program runs out, they find themselves in their species-specific non-breeding range. However, recent research suggests that this process might be significantly more complex. New data indicate that first-time migrants may not have a complete map but rather a system of beacons. This system could be based, for example, on geomagnetic cues or other cues that help first-year birds navigate their location along the migration route. To date, a significant body of evidence has been gathered to revise the classic ‘clock and compass’ program. It is likely that first-time migrants of many species (although perhaps not all) are capable of varying degrees of location control based on innate information. The question of what data sources they use and how precise their control remains open for further investigation.